Effects of neoadjuvant stereotactic body radiotherapy plus adebrelimab and chemotherapy for triple-negative breast cancer: A pilot study - Guanglei Chen; Xi Gu; Jinqi Xue; Xu Zhang; Xiaopeng Yu; Yu Zhang; Ailin Li; Yi Zhao; Guijin He; Meiyue Tang; Fei Xing; Jianqiao Yin; et al. (eLife, 2023)
Background: Emerging data have supported the immunostimulatory role of radiotherapy, which could exert a synergistic effect with immune checkpoint inhibitors (ICIs). With proven effective but suboptimal effect of ICI and chemotherapy in triple-negative breast cancer (TNBC), we designed a pilot study to explore the efficacy and safety of neoadjuvant stereotactic body radiotherapy (SBRT) plus adebrelimab and chemotherapy in TNBC patients. Methods: Treatment-naïve TNBC patients received two cycles of intravenous adebrelimab (20 mg/kg, every 3 weeks), and SBRT (24 Gy/3 f, every other day) started at the second cycle, then followed by six cycles of adebrelimab plus nab-paclitaxel (125 mg/m² on days 1 and 8) and carboplatin (area under the curve 6 mg/mL per min on day 1) every 3 weeks. The surgery was performed within 3–5 weeks after the end of neoadjuvant therapy. Primary endpoint was pathological complete response (pCR, ypT0/is ypN0). Secondary endpoints included objective response rate (ORR), residual cancer burden (RCB) 0-I, and safety. Results: 13 patients were enrolled and received at least one dose of therapy. 10 (76.9%) patients completed SBRT and were included in efficacy analysis. 90% (9/10) of patients achieved pCR, both RCB 0-I and ORR reached 100% with three patients achieved complete remission. Adverse events (AEs) of all-grade and grade 3–4 occurred in 92.3% and 53.8%, respectively. One (7.7%) patient had treatment-related serious AEs. No radiation-related dermatitis or death occurred. Conclusions: Adding SBRT to adebrelimab and neoadjuvant chemotherapy led to a substantial proportion of pCR with acceptable toxicities, supporting further exploration of this combination in TNBC patients. Funding: None. Clinical trial number: NCT05132790.